Ethical issues in aviation - Hoppe, Elizabeth (Ashgate, 2011)
Applied ethics has been gaining wide attention in a variety of curriculums, and there is growing awareness of the need for ethical training in general. Well-publicized ethical problems such as the Challenger disaster, the Ford Pinto case and the collapse of corporations such as Enron have highlighted the need to rethink the role of ethics in the workplace. The concept of applied ethics originated in medicine with a groundbreaking book published in 1979. Business ethics books began to appear in the 1980s, with engineering ethics following in the 1990s. This volume now opens up a new area of applied ethics, comprehensively addressing the ethical issues confronting the civil aviation industry. Aviation is unique in two major ways: firstly it has a long history of government regulations, and secondly its primary focus is the safety of its passengers and crew. For decades commercial aviation was viewed in the same manner as public utilities, and thus it was highly regulated by the government. Since the Deregulation Act of 1978, aviation has been viewed as any other business while other experts continue to believe that the sudden switch to deregulation has caused problems, especially since many airlines were unprepared for the change. "Ethical Issues in Aviation" focuses on current concerns and trends, to reflect the changes that have occurred in this deregulated era. The book provides the reader with an overview of the major themes in civil aviation ethics. It begins with theoretical frameworks, followed by sections on the business side of aviation, employee responsibility, diversity in aviation, ground issues regarding airports, air traffic control and security, as well as health and the environment. The contributors to the volume include both academics doing research in the field as well as professionals who provide accounts of the ethical situations that arise in the workplace.